Pemberdayaan UMKM Olahan Ikan Sebagai Upaya Peningkatan Pendapatan Keluarga - Ati Kusmiati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The Micro, small, and medium enterprises (MSMEs) that have been proven to exist until now in Ampel Village, Wuluhan are business that sell both fresh and processed fish. This business is carried out from generation to generation in a simple way. Therefore, it is necessary to empower MSMEs to increase their income and business activities. The used method is counselling and mentoring for merchant and fish processors. The activities results are as followed: (1) “BERKAH LANCAR SEJAHTERA” community of fish merchants and processors has been formed, but the number and activities are still limited. (2) The location of the community on Google maps, (3) Diversification of processed fish that has the potential to be developed in the form of shredded fish but is still constrained by marketing and infrastructure. Some of the community member products have implemented digital marketing by posting on social media (Facebook) and, (4) Food safety standards have not been fully implemented by merchants and fish processors. However, they have willing to carry out the correct method of food production gradually by their ability. The proposed suggestions are (1) community of fish merchants and processors can hold regular meetings, (2) objectify the production of processed products which more durable and promote them using online media, and (3) Apply the whole standard and procedures of food safety product, (4) Extend the time for MSMEs mentoring to reach improvement of MSMEs.